2014
DOI: 10.3151/jact.12.167
|View full text |Cite
|
Sign up to set email alerts
|

Kenaf Fiber Reinforced Polymer Composites for Strengthening RC Beams

Abstract: This paper presents the findings of an experimental study to investigate the structural behavior of reinforced concrete (RC) beams externally strengthened with various types of kenaf fiber reinforced polymer composite laminates with 50% fiber volume content. The experimental parameters including flexural strength, stress-strain relationship, deflection, tensile stress and young modulus of beams strengthened by different kenaf fiber reinforced polymer composites are discussed. In order to test the flexural stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Various investigations were conducted on kenaf, jute, jute rope fiber as polymer composites for both flexural and shear strengthening [5]. Hafizah et al [17] studied the flexural behaviour of RC beams externally strengthened by kenaf fiber reinforced polymer composites with 50% fiber volume content. The findings revealed that all strengthened beams managed to improve the flexural strength by 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations were conducted on kenaf, jute, jute rope fiber as polymer composites for both flexural and shear strengthening [5]. Hafizah et al [17] studied the flexural behaviour of RC beams externally strengthened by kenaf fiber reinforced polymer composites with 50% fiber volume content. The findings revealed that all strengthened beams managed to improve the flexural strength by 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Kenaf has a high potential to be the reinforcement material for bio-composite production due to its growth rate, and similar structure to jute and cotton which are the mostly used crop for fiber production [42]. Kenaf is an annual crop and its origin is Africa.…”
Section: Kenafmentioning
confidence: 99%
“…Some past studies have investigated the use of natural fibers as a composite to strengthen reinforced concrete (RC) beams in flexure and shear [24][25][26][27]. However, studies covering the use of bamboo as a fiber or laminate in strengthening and retrofitting RC concrete beams have not been overly reported.…”
Section: Introductionmentioning
confidence: 99%